Uptake of HIV pre-exposure prophylaxis and contraception in South African hair salons: a study protocol for a pilot cluster randomised controlled trial - Christina Psaros; Ingrid Bassett; Sabina Medal Govere; Jana Jarolimova; Joyce Yan; Sthabile Shezi; Lungile M Ngcobo; Shruti Sagar; Dani Zionts; Nduduzo Dube; RA Parker (BMJ Open)
Introduction Young women are disproportionately affected by HIV in South Africa and have a high incidence of unintended pregnancies. Access to sexual and reproductive health (SRH) services, including HIV pre-exposure prophylaxis (PrEP), contraception and screening for seally transmitted infections (STIs), remains limited in South Africa, in part due to inadequate infrastructure and individual barriers to care. Integrated, community-based SRH services have the potential to overcome barriers to clinic-based care for women at risk of HIV, unintended pregnancy and STIs. We are evaluating the feasibility, acceptability and preliminary effectiveness of a novel intervention offering PrEP, contraception and STI screening in hair salons.Methods and analysis We will conduct a pilot cluster randomised controlled trial in hair salons in urban KwaZulu-Natal, South Africa. Salons serving primarily female clients will be randomised either to an SRH service package (offer of PrEP, contraception, STI screening and health education) or to health education only. Interested female salon clients≥18 years old will be referred by trained stylists. In intervention salons, women who meet inclusion criteria will be offered HIV and pregnancy testing; if eligible, they will be offered oral PrEP, contraception (oral or injectable) and STI screening. Follow-up visits including monitoring side effects will be conducted at baseline and 3, 6, 9 and 12 months. We will measure intervention uptake as the proportion of eligible women who agree to salon-based PrEP and separately to salon-based contraception. We will assess feasibility by collecting process measures and evaluate retention as continued use of PrEP and contraception separately, defined as one additional visit within 6 months with continued use of PrEP and/or contraception.Ethics and dissemination The study has been approved by the University of KwaZulu-Natal Biomedical Research Ethics Committee and the Massachusetts General Brigham Institutional Review Board. The results will be disseminated to local and provincial Departments of Health, at scientific conferences and in peer-reviewed scientific journals.Trial registration number NCT04222504. Registered January 2020.